ANALISIS EFEKTIFITAS APLIKASI SIMAK BMN DALAM MENINGKATAN KUALITAS LAPORAN PENGGUNA BARANG PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN TALANG DUKU - Syamsurizal, Syamsurizal; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2017)
The purpose of this research is to analye the operators’ ability and the utilization of informationtechnology on the quality of user report. This research uses the technology Acceptance Model withvariable perceived ease of use, perceived usefulness, attitude to ward using, , perceived behaviorcontrol, behavior intrension to use system, to know the behavior of operator to the plane of dalaobtained from 75 operators of user of secure goods through questionnaires. Method of dataanalysis used research is result of data. The result of of analyze thre were only 7, hipothesiswereaccepted. Here below were the corelation was proof to be statisticaly significant : a)behavior intrension to use system and attitude to ward using, b) perceived ease of use and attitudetowards using, c) Behavior intrension to use system and subject norm, d) Behavior intrension touse system and perceived behavior control, e) perceived ease of use and attitude towards using, f)behavior intrension to use system and perceived usefullness, g) behavior intrension to use systemand perceived ease of use.